The Role of the IPS Lecturer in Building Character (Discipline, Honest and Responsible) in the Students of the IPS Education Program FITK UINSU Medan - Eka Susanti; Toni Nasution; Sari Kurniah Simamora (Universitas Muhammadiyah Enrekang, 2023)
Abstract This research aims to identify the role of Social Sciences (IPS) learning in building character (disciplined, honest and responsible) in students of the Social Sciences Tadris Study Program, Faculty of Tarbiyah Sciences (FITK) at the North Sumatra State Islamic University (UIN-SU) Medan, explaining the implementation social studies learning in building character (disciplined, honest and responsible) in students of the IPS Tadris Study Program FITK UIN SU Medan, and Analyzing the obstacles to social studies learning in building character (disciplined, honest and responsible) in students of the Tadris IPS Study Program FITK UIN SU Medan. This study uses a phenomenological approach in qualitative research methods. A qualitative approach was chosen to gain an in-depth understanding of the role of social studies learning in building character (discipline, honesty and responsibility) in students of the IPS Tadris Study Program FITK UIN SU Medan. The research objects consisted of the Dean of FITK, Head of the Study Program (Kaprodi) and Secretary of the IPS Study Program (Sekprodi), lecturers who taught at IPS and IPS students. The research results provide the answer that social studies learning can help build character by; 1) learning Social Values, 2) Understanding Social Context, 3) Analytical and Critical Ability, 4) Development of Speaking and Argumentation Skills, 5) Practical Experience and Community Service, 6) Case Study, and 7) Ethics Discussion. In its implementation, the Social Sciences Study Program carries out 1) Emphasis on Moral Values, 2) Formation of Moral Awareness, 3) Exemplary Model, 4) Discussion and Reflection, 5) Developing active-participative and creative-innovative learning models, 6) Implementing Habituation Programs, 7) Creation of a conducive and educative environment, and 8) Evaluation and sustainable use. Meanwhile, the obstacle factors in building character (such as discipline, honesty and responsibility) in students of the IPS Tadris Study Program at the Faculty of Tarbiyah and Teacher Training (FITK) UIN SU Medan can vary. These are several factors that may influence student character development in the context of social studies learning, namely: Curriculum and teaching methods, quality of human resources (lecturers), campus environment, student motivation and involvement, support from colleagues, community and family, infrastructure and systems. Evaluation. Keywords: Learning, Social Sciences, Character. PERAN DOSEN IPS DALAM MEMBANGUN KARAKTER (DISIPLIN, JUJUR DAN BERTANGGUNG JAWAB) PADA MAHASISWA PRODI PENDIDIKAN IPS FITK UINSU MEDAN Abstrak Penelitian ini bertujuan untuk mengidentifikasi peran pembelajaran Ilmu Pengetahuan Sosial (IPS) dalam membangun karakter (disiplin, jujur dan bertanggungjawab) pada mahasiswa Prodi Tadris IPS Fakultas Ilmu Tarbiyah (FITK) di Lingkungan Universitas Islam Negeri Sumatera Utara (UIN-SU) Medan, menguraikan pelaksanaan pembelajaran IPS dalam membangun karakter (disiplin, jujur dan bertanggungjawab) pada mahasiswa Prodi Tadris IPS FITK UIN SU Medan, dan Menganalisis kendala-kendala pembelajaran IPS dalam membangun karakter (disiplin, jujur dan bertanggungjawab) pada mahasiswa Prodi Tadris IPS FITK UIN SU Medan. Studi ini menggunakan pendekatan fenomenologi dalam metode penelitian kualitatif. Pendekatan kualitatif dipilih untuk mendapatkan pemahaman mendalam tentang peran pembelajaran IPS dalam membangun karakter (Disiplin, jujur dan bertanggungjawab) pada mahasiswa Prodi Tadris IPS FITK UIN SU Medan. Objek penelitian terdiri dari Dekan FITK, Kepala Program Studi (Kaprodi) dan Sekretaris Prodi (Sekprodi) IPS, Dosen-Dosen yang mengajar di IPS serta para mahasiswa IPS. Adapun hasil penelitian memberikan jawaban bahwa pembelajaran IPS dapat membantu membangun karakter dengan cara; 1) pembelajaran Nilai Sosial, 2) Pemahaman Konteks Sosial, 3) Kemampuan Analisis dan Kritis, 4) Pengembangan Keterampilan Berbicara dan Beragumentasi, 5) Pengalaman Pratikum dan Pengabdian Masyarakat, 6) Kajian Kasus, dan 7) Diskusi Etika. Adapun dalam Pelaksanaannya Prodi IPS melakukan 1) Penekanan Nilai Moral, 2) Pembentukan KesadaraN Moral, 3) Model Keteladanan, 4) Diskusi dan Refleksi, 5) Pengembangan Model pembelajaran aktif-partisifatif dan kreatif-inovatif, 6) Melaksanakan Program Pembiasaan, 7) Penciptaan Lingkungan yang kondusif dan edukatif, dan 8) Evaluasi dan Pemanfaatan berkelanjutan. Sedangkan Faktor-faktor kendala dalam membangun karakter (seperti disiplin, jujur, dan bertanggung jawab) pada mahasiswa Prodi Tadris IPS di Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN SU Medan dapat bervariasi. Ini adalah beberapa faktor yang mungkin mempengaruhi pembangunan karakter mahasiswa dalam konteks pembelajaran IPS yaitu: Kurikulum dan metode pengajaran, kualitas sumber daya manusia (Dosen), Lingkungan Kampus, Motivasi dan Keterlibatan Mahasiwa, Dukungan Teman Sejawat, Masyarakat dan Keluarga, Fasilitas Sarana Prasarana dan Sistem Penilaian. Kata Kunci: Pembelajaran, IPS, Karakter.